Reaction kinetics of the catalytic esterification of oleic acid with methanol - Tham, San Chin (2010)
Biodiesel is now considered as an alternative to liquid fuel from petroleum. The production of biodiesel from vegetable oils has been widely researched; however, it is not an economical process because of using valuable vegetable oils. Therefore, waste vegetable oil or animal fat are recommended as raw materials to produce biodiesel. However, the presence of moisture and free fatty acids (FFAs) in these materials may influence the performance and efficiency of such a process. Both water and FFAs can react with the catalyst rapidly and form long chain soaps, which may bring on serious separation problems; an esterification pretreatment step is generally required to decrease the FFAs amount to below 1 wt%. Therefore, the reaction kinetics of the reversible esterification reaction of oleic acid with methanol to methyl oleate is studied. The reaction was carried out in a 3-necked round bottom flask heated by a rotamantle which is the isothermal reactions are catalyzed by amberlyst ion exchange resin .Temperature was varied from 45-60˚C, molar ratio of methanol to oleic acid was varied from 4:1 , 8:1 , 12:1 , 16:1and catalyst loading was varied from 3g to 12g. The sample was withdrawn at certain time interval and it was analyzed using titration method. The conversion of oleic acid was increased when the parameters such as temperature, catalyst loading and molar ratio of methanol/acid was increased. The catalyst has exhibited maximum conversion (75.4wt.%) under the conditions of 55°C, methanol/oleic acid molar ratio of 16:1 and catalyst amount 12g. The experimental data is well fitted to the Pseudo-homogeneous model. This optimum operating condition and the kinetic model is useful for the designing the reactor size and pretreatment process for transesterification of triglycerides into esters.